2022
DOI: 10.3389/fgene.2022.871825
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Revealed the Freezing Tolerance Signaling Events in Winter Rapeseed (Brassica rapa L.)

Abstract: Winter rapeseed (Brassica rapa L.) is an important oilseed crop in northwest China. Freezing stress severely limits its production and geographical distribution, and frequent extreme freezing events caused by climate change are increasing the chances of winter freeze-injury. However, the underlying mechanism of B. rapa response to freezing stress remains elusive. Here, B. rapa genome (v3.0) was used as a reference for the comparative transcriptomic analysis of Longyou 6 and Tianyou 2 (strong and weak cold tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…found that all pathways, except for the MAPK signaling pathway-plant that is predominant in alfalfa, confer freezing stress ( Song et al., 2016 ; Wang et al., 2021 ). The MAPK signaling pathway has been reported as important in freezing signal transduction in many plants ( Cowan and Storey, 2003 ; Liu and Zhou, 2018 ; Wu et al., 2022 ), which means it could have a similar function in our study. As for SA application, the domain KEGG pathways were fatty acid elongation, biosynthesis of secondary metabolites, biosynthesis of amino acids, metabolic pathway, and MAPK signaling pathway-plant.…”
Section: Discussionsupporting
confidence: 65%
“…found that all pathways, except for the MAPK signaling pathway-plant that is predominant in alfalfa, confer freezing stress ( Song et al., 2016 ; Wang et al., 2021 ). The MAPK signaling pathway has been reported as important in freezing signal transduction in many plants ( Cowan and Storey, 2003 ; Liu and Zhou, 2018 ; Wu et al., 2022 ), which means it could have a similar function in our study. As for SA application, the domain KEGG pathways were fatty acid elongation, biosynthesis of secondary metabolites, biosynthesis of amino acids, metabolic pathway, and MAPK signaling pathway-plant.…”
Section: Discussionsupporting
confidence: 65%
“…Meanwhile, with the more frequent occurrence of extreme weather resulting from global climate change, the requirements of rapeseed's stress resistance have been greatly raised, especially when wintering. According to reports, cold stress includes chilling (0-15 • C) and freezing stress (<0 • C) [38], and the rapeseed in our study encountered an extremely long chilling stress period from 28 November 2022, to 8 February 2023 (Figure 1D). The seed germination and seedling emergence stages of rapeseed are the most sensitive to abiotic or biotic stress, which directly determines a rapeseed population's density and grain yield [39].…”
Section: Discussionmentioning
confidence: 50%
“…Our previous studies have revealed that ROS accumulation and response speed are critical for freezing tolerance in B. rapa [31,38]. To further explore the relationship between BrICE1 and BrICE2 involvement in low-temperature resistance and ROS, we assayed ROS accumulation in BrICE1 and BrICE2 transgenic plants using nitroblue tetrazolium (NBT) histochemical staining after chilling (at 4 ℃ for 3 or 6 h) or freezing treatment (at -4 ℃ for 3 or 6 h).…”
Section: Brice1 and Brice2 Overexpression Enhances Ros Scavenging By ...mentioning
confidence: 99%
“…Arabidopsis thaliana ecotype Col-0 and transgenic seedlings used in this study were grown on half-strength MS medium supplemented with 1% sucrose and 0.8% agar at 22 ℃ under a 16-h light/8h dark photoperiod. For soil growth, Arabidopsis and B. rapa seeds were vernalized at 4 ℃ for 3 d and then grown at 22 ℃ in a greenhouse under a 16-h light/8-h dark cycle condition [31,38].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%